Process flow improvement in production of noise filter products through lean manufacturing technique - Rattarak Moonpragarn (2018)
© 2018 IEEE. This research has applied Lean Manufacturing Technique to improve process flow in the manufacture of noise filter products at a case study company. The research procedure started from studying the process and process times at every step in the manufacture of noise filter products. After this was written the current state value stream map to study the overall picture and indicate main problems in the process. From there was conducted brainstorming with the relevant personnel to identify areas of waste. Then methods were proposed to adjust the process, using Line Balancing technique which specified the working time of a semi-automatic soldering machine to determine the cycle time of the process. Adjustments were made to the layout design and to reduce the time used to move components and work pieces. Also, equipment was designed to speed up the work. From there was written the future state value stream map. Once the methods had been applied, it was found that the efficiency of the production line was increased from 56.9% to 85.76%, and staff reduced from 16 to 11, while maintaining production to meet customer demand. Moreover, work in process was reduced by 69.28%, waiting time reduced by 38.91%, working space reduced by 46.91%, the movement of components and work pieces reduced by 56.25%, and non-value added time reduced from 93.92% to 85.64%.